1997
DOI: 10.1097/00006842-199705000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects of Blood Pressure Biofeedback Treatment on Hypertension by Auto-shaping

Abstract: This treatment was effective in suppressing the pressor response to stress. Patients whose blood pressure increases with stress may be suited for biofeedback intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 27 publications
1
17
0
1
Order By: Relevance
“…1,2 Relaxation and stress-relieving techniques such as yoga, meditation and biofeedback have also been shown capable of lowering BP. [3][4][5][6][7][8][9][10][11][12] However, the results of these behavioural-based treatments have not been uniform and the mechanisms by which they lower BP are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Relaxation and stress-relieving techniques such as yoga, meditation and biofeedback have also been shown capable of lowering BP. [3][4][5][6][7][8][9][10][11][12] However, the results of these behavioural-based treatments have not been uniform and the mechanisms by which they lower BP are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the patient learns to identify sensations that accompany reductions in blood pressure and, after several training sessions, the patient may be able to develop skills to maintain control of blood pressure. The type of information given to patients may differ; as well as direct blood pressure biofeedback measures, 15 other indirect indicators may be used including thermal (TBF), 16 galvanic skin response (GSR), 17 heart rate (HR) 18 and electromyographic (EMG) activity. 19 In TBF the patient is given information regarding the temperature of their finger or toe and instructed to warm their hands or feet in relation to this feedback.…”
Section: Biofeedbackmentioning
confidence: 99%
“…Intention-totreat (ITT) analyses were not specifically reported in any trial; thus, ITT was assumed in cases in which it appeared that all patients randomly assigned to one of the treatment groups were included in the final analysis whether or not they completed or received that treatment. 15 was reported, trials were frequently supported by grants from independent sources; only two trials 40,42 reported some funding support from a pharmaceutical company. The commonly cited primary outcome of the trials was the effect of the interventions on direct measures of blood pressure, although the primary outcome in two trials 58,62 was the reduction in medication from two antihypertensive drugs to one.…”
Section: Quality Assessment Of Included Trialsmentioning
confidence: 99%
See 2 more Smart Citations